Mathematics and Islamic Thought: Seeing Relationship Between Mathematics and Islamic Teaching Resources - Eliva Sukma Cipta; Muhammad Hori (International Journal of Nusantara Islam, 2018)
This article tries to discuss about mathematics and islamic thought.  By seeing the relationship between mathematics and islamic teaching resources, this article found that science in this world can be classified into three groups, namely natural sciences, social science, and humanities. The natural sciences which consist purely consist of physics, chemistry, and biology, and some people enter mathematics again. The social sciences that fall into the category of pure sciences include sociology, anthropology, psychology, and history. Whereas the humanities consist of philosophy, language and literature, and art. Qur’an and Hadith in the development of science are positioned as sources of qawliyyah verses while the results of observations, experiments, and logical reasoning are positioned as sources of kauniyyah verses. With its position like this, then various branches of knowledge can always be sought from the source of the Qur'an and Hadith. Like, the science of mathematics developed on the basis of the Qur'an and Hadith sources as well as the results of observation, experimentation, and logical reasoning. Mathematics itself has a very close relationship with the spiritual traditions of Muslims, is familiar with the Qur'an, and of course mathematics can also be used as a "path" towards achieving happiness benefits both in this world and the hereafter.